2018
DOI: 10.3928/23258160-20181002-13
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Difference of Choroidal Vasculature Between Polypoidal Choroidal Vasculopathy and Neovascular AMD on OCT: From the Perspective of Pachychoroid

Abstract: BACKGROUND AND OBJECTIVE: To investigate the morphological difference of choroidal vasculature between polypoidal choroidal vasculopathy (PCV) and neovascular age-related macular degeneration (nAMD) on optical coherence tomography (OCT). PATIENTS AND METHODS: One hundred eighty-nine patients with macula-involved PCV (n = 107) or nAMD (n = 82) were retrospectively reviewed. The subfoveal choroidal thickness (SFCT) and thickness of the Haller's layer were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Recent reports have included PCV in the pachychoroid spectrum [27]. The present study confirmed the presence of thick choroids in patients with PCV in Caucasians, as previously described in Asians [28].…”
Section: Discussionsupporting
confidence: 91%
“…Recent reports have included PCV in the pachychoroid spectrum [27]. The present study confirmed the presence of thick choroids in patients with PCV in Caucasians, as previously described in Asians [28].…”
Section: Discussionsupporting
confidence: 91%
“…PCV associated with pachychoroid should therefore be differentiated from similar neovascularization associated to AMD [10,11,14] and it should be indicated as PPCV. Based on Gass classi cation, PCV is considered a type 1 subretinal neovascularization which grows underneath the RPE [15].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 This might explain the rarity of combined PCV and RP, because PCV is considered to belong to the pachychoroid spectrum disorders of the macula. 5 Contrarily, decreased choroidal thickness has been reported in classic macular choroidal neovascularization (CNV), a change that might be considered more compatible with RP. There are two previous reports of RP cases that developed classic CNV, both of which responded well to intravitreal bevacizumab.…”
Section: Discussionmentioning
confidence: 99%